Lubricant, lubricating composition and sliding machine
The new lubricant, with its aminoalkyl groups, addresses the instability of sliding properties in existing lubricants by forming a strong adsorption film, achieving improved wear resistance and reduced friction.
Patent Information
- Application Number
- JP2022079876
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-05-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-05-16
AI Technical Summary
Existing lubricants do not effectively stabilize sliding properties by forming a stable adsorption film on sliding surfaces, leading to inadequate wear resistance and friction reduction.
A new lubricant with a specific chemical structural formula, featuring two aminoalkyl groups, is developed to form a stable adsorption film on sliding surfaces, enhancing wear resistance and reducing friction.
The lubricant quickly forms a strong adsorption film on sliding surfaces, stabilizing sliding characteristics, reducing wear, and lowering friction, even under high surface pressures.
Smart Images

Figure 0007666399000005 
Figure 0007666399000006 
Figure 0007666399000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a lubricant and the like. [Background technology]
[0002] Machines with sliding parts are designed to have a longer life and reduce losses (improved efficiency) by reducing wear and friction. Such sliding characteristics are greatly influenced by the lubricant (including compositions such as lubricating oil) supplied to (interposed between) the sliding parts. For this reason, many proposals have been made regarding lubricants, and for example, there are related descriptions in the following patent documents. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2002-338983 [Patent Document 2] Patent Publication No. 2022-24803 Summary of the Invention [Problem to be solved by the invention]
[0004] Patent Document 1 proposes a lubricating composition having excellent rust-preventing performance. Patent Document 2 proposes a lubricating composition for diesel engines having a desired viscosity.
[0005] These patent documents contain no description or suggestion relating to the adsorptivity of a lubricating composition on a sliding surface or the film formed on the sliding surface.
[0006] The present invention has been made in view of the above circumstances, and has an object to provide a new lubricant or the like that can stabilize sliding characteristics. [Means for solving the problem]
[0007] As a result of intensive research into solving this problem, the inventors have developed a lubricant with a new structure that has excellent adhesion to sliding surfaces. By expanding on this result, the present invention, which will be described below, has been completed.
[0008] Lubricants (1) The present invention is a lubricant represented by the following chemical structural formula:
[0009] [ka] (R: a hydrocarbon group having 8 to 24 carbon atoms, m and n: integers of 2 to 8)
[0010] (2) When the lubricant of the present invention is used in sliding machines, a stable adsorbed film can be formed on the sliding surface, thereby stabilizing the sliding characteristics.
[0011] The reason and mechanism by which the lubricant of the present invention exhibits such excellent effects are not necessarily clear, but it is currently believed to be as follows. As shown in chemical structural formula (1), the lubricant of the present invention has two aminoalkyl groups. These functional groups allow the lubricant of the present invention to be adsorbed to the surface of a substrate (e.g., steel) more stably than before. As a result, when the lubricant of the present invention or a composition thereof is supplied to the sliding part (between sliding surfaces) of a sliding machine, a strong adsorbed film is quickly formed on at least one of the sliding surfaces (e.g., immediately after the start of operation of the sliding machine), and the desired sliding characteristics (wear resistance, low friction, etc.) can be stably ensured.
[0012] 《Lubricating composition》 The present invention can also be understood as a lubricating composition containing the above-mentioned lubricant. The lubricating composition is, for example, a liquid phase (mixed liquid) containing a lubricant. be. A typical example of a lubricating composition is a lubricating oil in which the lubricant is added to a base oil.
[0013] Sliding Machine The present invention can also be understood as a sliding machine having a sliding surface to which the above-mentioned lubricant is supplied. The lubricant is supplied to the sliding surface as, for example, lubricating oil. Representative examples of the sliding machine include an engine and a transmission, and the lubricant is supplied to the sliding surface as an additive to engine oil or transmission oil (including automatic transmission fluid (ATF)).
[0014] "others" (1) The hydrocarbon groups R and R' in this specification may be saturated or unsaturated groups, and may be straight-chain or branched groups.
[0015] (2) Unless otherwise specified, "x to y" in this specification includes a lower limit value x and an upper limit value y. Any numerical value included in the various numerical values or numerical ranges described in this specification may be used as a new lower limit or upper limit value to create a new range such as "a to b". Furthermore, unless otherwise specified, "x to y ppm" in this specification means x ppm to y ppm. The same applies to other unit systems. [Brief description of the drawings]
[0016] [Figure 1A] FIG. 2 is an explanatory diagram showing a first synthesis step of a lubricant (one example). [Figure 1B] FIG. 2 is an explanatory diagram showing the second synthesis step. [Diagram 2] FIG. 2 is a spectrum diagram showing an example of an analysis of a lubricant by 1H-NMR. [Diagram 3] FIG. 1 is a schematic diagram of a cross-pin wear test. [Figure 4] 1 is a graph showing the relationship between the insulation ratio and time obtained by the abrasion test. [Figure 5A] 4 is a photograph showing the wear marks obtained by the wear test. [Figure 5B] 1 is a bar graph showing the wear scar width. [Figure 6] FIG. 1 is a spectrum diagram showing an example of analysis of a wear mark surface by TOF-SIMS. [Figure 7] 1 is a table and a bar graph showing standard values of peak areas obtained by TOF-SIMS. [Figure 8] 1 is a bar graph showing the relationship between the number of carbon atoms in an aminoalkyl group in an additive molecule and the interaction energy of the additive molecule with an Fe(100) surface. [Figure 9] This is a model diagram illustrating the adsorption of the additive molecules to the FeO(110) surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] One or more components selected from the present specification may be added to the above-mentioned components of the present invention. The contents described in this specification may apply not only to lubricants and lubricating compositions, but also to sliding machines and sliding members. Components related to the manufacturing method may also be components related to the product. Which embodiment is best depends on the target, required performance, etc.
[0018] Lubricants The lubricant is composed of a molecule represented by the chemical structural formula (1). R constituting the main chain of this molecule is a hydrocarbon group having 8 to 24, 12 to 22, or even 16 to 20 carbon atoms. The hydrocarbon group may be a saturated or unsaturated hydrocarbon group. Examples of the hydrocarbon group constituting the main chain include alkyl groups such as oleyl, 2-ethylhexyl, n-octyl, isooctyl, nonyl, decyl, undecyl, dodecyl, lauryl, tridecyl, pentadecyl, hexadecyl, palmitoleyl, heptadecyl, octadecyl, stearyl, linoleyl, nonadecyl, tetradecyl, and arachidyl, or unsaturated alkyl groups (alkenyl groups).
[0019] The two functional groups (alkylamines) in chemical structure (1) may have the same or different carbon numbers. Usually, if the carbon numbers are the same (m=n), it is easier to synthesize the lubricant.
[0020] The molecule represented by chemical structural formula (1) can be, for example, determined by proton nuclear magnetic resonance spectroscopy ( 1When analyzed by H-NMR, the chemical shift values of the spectrum showing Ha and Hb shown in the following chemical structural formula (2) can be around 2.4 ppm and around 2.6 ppm, respectively. 2 ) and the number of carbon atoms in R' is the number of carbon atoms in R minus 1.
[0021] [ka]
[0022] 《Organic film》 An organic film derived from the lubricant may be formed on the sliding surface to which the lubricant is supplied. This organic film may be formed only from the molecules shown in chemical structural formula (1), or may be generated by the reaction of these molecules with surrounding molecules (e.g., the constituent molecules of the base oil). Although the mechanism of its formation is unclear, it is thought that two functional groups (alkylamines) in the lubricant molecules are firmly and quickly adsorbed to the sliding surface (substrate surface), forming an organic film with excellent sliding properties.
[0023] The presence or absence of an organic film can be determined based on the profile (position and magnitude of the spectrum) obtained by performing positive ion spectrum analysis on the sliding surface in contact with the lubricant using time-of-flight secondary ion mass spectrometry (TOF-SIMS). The detection sensitivity (peak intensity / peak area) by TOF-SIMS tends to vary from sample to sample. Quantitative analysis of the organic film is possible by using the intensity (reference area) of a specific peak obtained for each sample as a standard and evaluating the intensity (area) of other peaks (i.e., normalizing by the reference area).
[0024] An example of such a reference peak is the peak around m / z 29.04 (C 2 H 5 + ) peak. The peak area (S 0 / reference area), the organic film has a peak at around m / z 30.03 (CH 4 N + ) peak area (S 1 ) is 1.5 times or more (S 1 / S 0 ≧1.5 ) and more than doubled, at around m / z 70.07 (C 4 H 8 N + ) peak area (S 2 ) is 0.3 times or more (S 2 / S 0 ≧0.3) and even more than 1x, at around m / z 84.08 (C 5 H 10 N + ) peak area (S 3 ) is 0.1 times or more (S 3 / S 0 ≧0.1) and even 0.5 times or more.
[0025] In addition to these peaks, for example, the peak area (S 4 ) and the peak area around m / z 349.35 (S 5 ) is 0.01 times or more the standard area (S 4 / S 0 ≧0.01, S 5 / S 0 ≧0.01) or even 0.02 times or more. The specific molecular structures of the positive ions detected near m / z 323.32 and near m / z 349.35 are not clear, but because the decimal points of their mass numbers (0.32 and 0.35) are on the positive side of the integer values (323 and 349), they are judged to be made of organic matter that does not contain metal elements.
[0026] Around m / z29.04 (C 2 H 5 + ), in addition to the peak area around m / z27.02 (C 2 H 3 + ) or the total area of each peak (total ion amount) may be used as the standard. In the sample analyzed this time, the peak area around m / z 29.04 was larger than the peak area around m / z 27.02, so the peak area around m / z 29.04 (C 2 H 5 + ) was used as the reference area.
[0027] <Lubricant composition / sliding machine> Examples of lubricating compositions include engine oils and transmission oils (including ATFs) in which a lubricant is added to a base oil. Examples of sliding machines include engines and transmissions. The lubricant of the present invention can quickly form an organic adsorption film on the sliding surface, so it is also suitable for low-viscosity lubricating compositions and sliding machines operated in low temperature ranges (e.g., transmissions, internal combustion engines dedicated to hybrid vehicles, etc.).
[0028] The amount of the lubricant added may be adjusted as appropriate, but may be, for example, about 0.001 to 10 mass%, 0.01 to 5 mass%, or even 0.1 to 3 mass% based on the total amount of the lubricant composition. The lubricant composition may contain a plurality of types of molecules (molecules having different carbon numbers (molecular weights) or structures (including isomers)) belonging to chemical structural formula (1). The lubricant composition may contain additives other than the lubricant of the present invention. EXAMPLES
[0029] The present invention will be described in more detail with reference to specific examples of lubricants and the like.
[0030] Lubricants (1)Synthesis As shown in Figure 1A and Figure 1B (collectively referred to as "Figure 1"), oleylamine (C 18 H 37 N) as the starting material, bisaminoalkylamine (C 26 H 55 N 3 / R=C 18 H 35 , m = n = 4) was synthesized. The details are as follows.
[0031] First, as shown in FIG. 1A, an intermediate bisphthalimide was produced from oleylamine as follows (first synthesis step). In an argon gas atmosphere, oleylamine, N,N-dimethylformamide (DMF dehydrated), phthalimide (N-(4-Bromobutyl)phthalimide), sodium bicarbonate (NaHCO 3The mixture was heated to an internal temperature of 100° C. and stirred overnight to complete the reaction.
[0032] The reaction mixture was cooled to room temperature and diluted with city water (1 L) and ethyl acetate (AcOEt: 1 L). After removing the aqueous layer by separation, the organic layer was washed with city water (0.5 L) and saturated saline (0.5 L). 2 SO 4 The drying agent was filtered off, and the filtrate was concentrated to obtain a crude product (24 g). The crude product was purified by column (SiO 2 The reaction mixture was mixed with toluene / acetone (4 / 1) to obtain a pale yellow oily bisphthalimide compound (14.2 g).
[0033] Next, as shown in FIG. 1B, a bisaminoalkylamine was produced from the bisphthalimide as follows (second synthesis step). Under an argon gas atmosphere, the bisphthalimide, tetrahydrofuran (THF), and ethanol (EtOH) were charged into a reaction vessel (1 L) and stirred to obtain a homogeneous solution. Hydrazine hydrate (N 2 H 4 H 2 O) was added and the mixture was stirred overnight under heating and reflux. After confirming the disappearance of the bisphthalimide by thin layer chromatography (TLC), the reaction was terminated. The reaction solution was allowed to cool to room temperature, and the precipitated solid was filtered off. The filtrate was concentrated to obtain a crude product (11.6 g). This crude product was purified by column purification (SiO 2 : 50g, MeOH only → 8M NH 3 / MeOH) to give a nearly colorless oily bisaminoalkylamine (6.54 g).
[0034] (2) Structural analysis The synthesized bisaminoalkylamine 1 The spectrum obtained by H-NMR analysis is shown in Figure 2. The solvent was deuterated methanol (CD 3The analysis was carried out at NARD Laboratory, Inc. using a FT-NMR manufactured by JEOL Ltd. at a measurement frequency of 400 (399.65) MHz.
[0035] As is clear from Figure 2, Main chain (alkylamine) The hydrogen (Ha) close to the nitrogen (N) of the amino group has a peak at around 2.4 ppm. two Hydrogen (Hb), which is close to nitrogen (N), had a peak at around 2.6 ppm.
[0036] "verification" The sliding properties of the synthesized bisaminoalkylamine (bisaminobutyl substituted product) were verified by the following wear test.
[0037] (1) Lubricating oil A lubricating oil was prepared by blending bisaminoalkylamine at a ratio of 0.04 mol / kg with a hydrocarbon base oil (Group III base oil / YUBASE2, SK manufactured by Lubricants) (Sample 1). For comparison, a lubricating oil was also prepared by blending oleylamine instead of the bisaminoalkylamine (Sample C1).
[0038] (2) Abrasion test A cross-pin wear test, shown in Figure 3, was conducted using each sample lubricant (test oil). This wear test was conducted by pressing a rotating pin against another pin at right angles. Both pins were cylindrical (φ20mm) made of steel (SCM420) with carburized surfaces. The pin had a total length of 150mm, but the central section (length 10mm) used for analysis was split (replaceable).
[0039] The pressing load between both pins was 20N, and the sliding speed was maintained at 1.2 m / S for 45 minutes, after which the sliding speed was decelerated in descending order from 1.0 m / S, 0.7 m / S, 0.5 m / S, 0.3 m / S, 0.2 m / S, and 0.1 m / S. After the deceleration started, the holding time for each sliding speed was 3 minutes. Lubricant was supplied to the sliding part at about 5 mL / min by a rotary pump. To confirm reproducibility, the same test was repeated three times for each sample. Unless otherwise specified, the sliding characteristics of each sample were evaluated using the average value obtained from the three tests.
[0040] (3) Insulation A voltage (50 mV) was applied between both pins, and the voltage value that changed due to the insulating film that formed between the two pins was measured. The change in voltage value during the test was converted into an insulation rate (%) and is shown in Figure 4. The insulation rate is the electrical resistance value (initial value: r 0 ) fluctuation rate {100 × (rr 0 ) / r 0}.
[0041] As is clear from Fig. 4, when the lubricating oil containing bisaminoalkylamine (sample 1) was supplied to the sliding part, the insulation rate increased rapidly immediately after the start of the wear test. On the other hand, when the lubricating oil containing oleylamine (sample C1) was supplied to the sliding part, the insulation rate did not increase until 15 minutes or more had passed since the start of the test.
[0042] In the case of sample 1, it is believed that an insulating film (organic film) was quickly adsorbed and formed on the sliding surface. As the sliding speed slows down, the film formed on the sliding surface becomes thinner, and the shared load increases, making it easier to detach (peel off). For this reason, it is believed that the insulation rate also decreases as the sliding speed slows down. However, the decrease in insulation rate of sample 1 is more gradual than that of sample C1, and a considerable insulation rate was maintained even in the range where the sliding speed is 0.5 m / s or less. In other words, it was found that by using the lubricant of sample 1, an organic film is quickly and stably formed on the sliding surface.
[0043] (4) Wear marks A photograph of the appearance of the wear mark (one example) on the fixed pin side after the wear test is shown in Fig. 5A, and the wear mark width (average value of three values) is shown in Fig. 5B. The wear mark width is the maximum length in the short direction (longitudinal direction of the rotation pin) formed on the surface of the fixed pin.
[0044] As is clear from FIG. 5A and FIG. 5B (both of which are collectively referred to as "FIG. 5"), sample 1 had smaller wear marks and less surface roughness than sample C1.
[0045] The area of the wear mark of sample 1 was approximately half or less that of the wear mark of sample C1. Therefore, it is considered that the substantial pressure acting between the sliding surfaces of sample 1 was greater than that of sample C1. It was also found that even under such high surface pressure, the lubricant of sample 1 stably formed an organic film on the sliding surface.
[0046] (5) Adsorption film The surface of each wear mark after the cross-pin test was analyzed using a TOF-SIMS device (Time-of-Flight Secondary Ion Mass Spectrometry / TRIFT V nanoTOF manufactured by ULVAC-PHI, Inc.). 3 ++ The center of each wear mark was analyzed in high mass resolution measurement mode using a 250 μm×250 μm analysis area for sample 1 with small wear marks, and a 300 μm×300 μm analysis area for sample C1 with large wear marks.
[0047] The positive ion spectra thus obtained for each sample are shown in FIG. 6. The vertical axis scale of the spectra shown in FIG. 6 is the scale of hydrocarbon ions (C 2 H 5 + ) was adjusted based on the ionic strength of
[0048] The peak area of the representative fragment (S) is calculated by multiplying the peak area of the standard fragment (S 0 The secondary ion intensity ratio normalized by the reference area (S / S 0) are summarized in Figure 7. As a representative fragment suitable for quantitative analysis, we focused on hydrocarbon groups, which are less dependent on additives in the oil itself and can be detected over a wide range.
[0049] Standard area (S 0 ) has a peak at m / z 29.04 (C 2 H 5 + ), in addition to the peak area around m / z27.02 (C 2 H 3 + The peak area of each peak and the total ion amount (sum of all peak areas) were also used. Figure 7 shows the normalized secondary ion intensity ratio in both table form and bar graph. Each peak area was calculated using the analysis software attached to the TOF-SIMS device.
[0050] As is clear from FIGS. 6 and 7, sample 1 has a higher peak density at around m / z 30.03 (CH 4 N + ) peak area (S 1 ), around m / z 70.07 (C 4 H 8 N + ) peak area (S 2 ) and the peak area around m / z 84.08 (S 3 ) became larger. Around m / z29.04 (C 2 H 5 + ) peak area (S 0 In terms of the intensity ratio based on the standard, for sample 1, S 1 / S 0 ≒2.43(≧1.5), S 2 / S 0 ≒1.67(≧0.3), S 3 / S 0 ≒0.89 (≧0.1). On the other hand, in the case of sample C1, S 1 / S 0 ≒1.2, S 2 / S 0 ≒0.21, S 3 / S 0 ≒0.095. These values were significantly smaller than those of sample 1.
[0051] In addition, in sample 1, the peak near m / z 110 (C 7 H 12 N + ), characteristic peaks appeared around m / z 323.32 and around m / z 349.35, which were not observed in sample C1.
[0052] It is believed that the formation of an adsorption film derived from organic components that shows such secondary ion peaks on the substrate surface (sliding surface) results in the development of excellent adsorptive properties and sliding characteristics (wear resistance, etc.).
[0053] "supplement" Based on the above results, the alkyl chain length of bisaminoalkylamines (m, n in chemical structural formula (1)) was examined by molecular dynamics using molecular calculation software (Materials Studio / Forcite Plus, Dassault Systèmes).
[0054] As shown in Figure 8, it was found that the longer the alkyl chain length of the bis(aminoalkyl) group of a molecule, the more negative the interaction energy with the metal surface (Fe(100) surface) becomes (i.e., the more stably the molecule is adsorbed).
[0055] However, molecules with excessively long chains are likely to cause steric hindrance when added to base oil, and are expected to reduce the adsorptivity to the substrate surface. Therefore, the adsorptivity of each molecule in a mixed system with base oil was evaluated by Amorphous Cell calculation using the molecular calculation software mentioned above.
[0056] A mixture of 80 additive molecules and 120 base oil (isododecane) molecules (density: 0.8 g / cm 3 The state of the Fe 200mm x 200mm substrate surface 10 ns after contact with the substrate surface is shown in Fig. 9. O (1 1 0) plane, the number of carbon atoms in the alkyl chain of the bis(aminoalkyl) group is 4 (C 4 ), the number of carbon atoms is 6 (C 6It was confirmed that the rate of adsorption of additive molecules to the substrate surface (sliding surface) was higher than when m (m) or n (oleylamine) was used. From these results, it can be said that the number of carbon atoms in the alkyl chain length (m, n) is preferably around 4, that is, 2 to 8, or even 3 to 6. Note that m and n may be different integers, but it is easier to synthesize the additive (lubricant) if they are the same integer.
Claims
1. A lubricant with the chemical structure shown below. 【Chemistry 1】 (R: a hydrocarbon group having 8 to 24 carbon atoms, m and n: integers of 4 to 6)
2. Proton nuclear magnetic resonance spectroscopy ( 1 The chemical shift value of the spectrum obtained by H-NMR is around 2.4 ppm. a and H near 2.6 ppm b 2. The lubricant of claim 1, having the following chemical structure: 【Chemistry 2】 (R': carbon number 7 to 23)
3. A lubricating composition comprising the lubricant of claim 1 or 2.
4. A sliding machine comprising a sliding surface to which the lubricant according to claim 1 or 2 is supplied.
5. When the positive ion spectrum was analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the peak was observed around m / z 29.04 (C 2 H 5 + ) peak area (S 0 5. The sliding machine according to claim 4, wherein an organic film that satisfies the following criteria is provided on the sliding surface with respect to a reference area of said sliding surface: Around m / z 30.03 (CH 4 N + ) peak area (S 1 ) is 1.5 times or more of the reference area (S 1 / S 0 ≧1.5), Around m / z 70.07 (C 4 H 8 N + ) peak area (S 2 ) is 0.3 times or more the reference area (S 2 / S 0 ≧0.3), Around m / z 84.08 (C 5 H 10 N + ) peak area (S 3 ) is 0.1 times or more the reference area (S 3 / S 0 ≧0.1)
6. The organic film further has a peak area (S 4 ) is 0.01 times or more of the reference area (S 4 / S 0 6. The sliding machine according to claim 5, wherein the ratio of the friction coefficient to the friction coefficient is 0.01 or more.
7. The organic film further has a peak area (S 5 ) is 0.01 times or more of the reference area (S 5 / S 0 6. The sliding machine according to claim 5, wherein the ratio of the friction coefficient to the friction coefficient is 0.01 or more.
Citation Information
Patent Citations
Low sulfur automatic transmission oil having improved wear-resistant lubricating characteristics
JP2002309280A
Lubricating oil composition
JP2002338983A
Lubricant and lubricating composition
JP2003119483A
Marine engine lubricant
JP2016521308A
Aliphatic triamine-based lubricant composition
JP2016540867A